2021
DOI: 10.1007/s13577-020-00474-z
|View full text |Cite
|
Sign up to set email alerts
|

MiR-27b-3p inhibits the progression of renal fibrosis via suppressing STAT1

Abstract: Renal fibrosis is a pathologic change in chronic kidney disease (CKD). MicroRNAs (miRNAs) have been shown to play an important role in the development of renal fibrosis. However, the biological role of miR-27b-3p in renal fibrosis remains unclear. Thus, this study aimed to investigate the role of miR-27b-3p in the progression of renal fibrosis. In this study, HK-2 cells were stimulated with transforming growth factor (TGF)-β1 for mimicking fibrosis progression in vitro. The unilateral ureteric obstruction (UUO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…It can inhibit the translation of many genes into proteins, causing the abnormal function of a large number of genes [26]. Commonly, it generally plays a role in anti-cancer genes in tumors [48][49][50]. In this investigation, we found that miR-27b-3p inhibits HCC cell proliferation and invasion.…”
Section: Discussionmentioning
confidence: 61%
“…It can inhibit the translation of many genes into proteins, causing the abnormal function of a large number of genes [26]. Commonly, it generally plays a role in anti-cancer genes in tumors [48][49][50]. In this investigation, we found that miR-27b-3p inhibits HCC cell proliferation and invasion.…”
Section: Discussionmentioning
confidence: 61%
“…It has been demonstrated and confirmed in many studies that lncRNAs can affect the development of gliomas by combining with miRNAs [30,35]. Some literatures have confirmed that miR-27b-3p was related to the development of a variety of tumors, including glioma, colorectal cancer, and endometrial cancer [2,15,20,33]. Miao and his colleagues found that miR-27b-3p inhibited the development of glioma by targeting YAP1.…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, IL-1β-mediated activation of the TrkB/CREB pathway could induce chondrocyte apoptosis. Emerging evidence has suggested that the inhibition of the TrkB/CREB pathway exerts a bene cial role in KOA (33)(34)(35). Herein, cell transfection with miR-27b-3p mimics inhibited the activation of the TrkB/CREB pathway.…”
Section: Discussionmentioning
confidence: 93%